Spectrum enhanced colour ultrasound (SECU) imaging. (15th March 2020) - Ma, Jianguo; Wei, Min; Xie, Zhun; Huang, Shan; Chen, Boya; Qiu, Yang; Wang, Yueli; Li, Yulin; Du, Jie; Xu, Lijun
Graphical abstract: Highlights: Different tissues/organs exhibited various spectral patterns. The spectral variation was used to enhance colour contrast. Colour-coding of the spectral patterns helped interpretation of the images. Abstract: Conventional ultrasound imaging presents the amplitude of scattering and reflecting signals by brightness whereas neglecting the spectral information. However, ultrasonic harmonic imaging demonstrated that ultrasonic signals carry abundant and various spectral information. In this research, we propose a spectrum enhanced colour ultrasound imaging method that elucidates ultrasonic spectral patterns in ultrasound images. First, continuous wavelet transform upon the ultrasound signals exhibited the spectra at various positions. Second, principal component analysis concentrated major information within the first dimensions. Third, the dataset was projected into the eigenspace, and the coordinates were colour-coded to make colour ultrasound images. The technique differentiated tissues based on their spectral patterns, which may lead to easy interpretation of ultrasound images, pioneering an advanced approach in the future.